Educação jurídica popular: identidade e protagonismo de novos sujeitos de direito - Souza, Sirley Aparecida de (2019)
This thesis results from an investigation of the formation process of the Popular Jurist, developed in the research of Work, Education and Social Movements, of the UFG Graduate Program in Education, with the objective of knowing and understanding, from the field concepts (Law, Power, Legal) and State, by Pierre Bourdieu, the Popular Jurist, the training entities (Association of Rural Land Workers Lawyers / AATR / BA and the Human Rights Defense Foundation Margarida Maria Alves / FDDHMMA / PB), the curriculum, methodologies, the teaching and learning process and the impacts of this legal knowledge on the communities of the investigated subjects. The research initially operated by the documentary and bibliographic way and, complementarily, with the contribution of oral documentation. The results show that there are Non-Government entities proposing and developing, through Paulo Freire's methodology, the disengagement of the Law through a Liberating Popular Legal Education; and the beneficiaries declare that they could access their rights without intermediaries. Finally, it is possible to think about the Law and Popular Legal Education in another aspect, other than that proposed by the official teaching structure.